The Vegetarian: A Novel (Random House Publishing Group, 2016)
WINNER OF THE INTERNATIONAL BOOKER PRIZE • “[Han] Kang viscerally explores the limits of what a human brain and body can endure, and the strange beauty that can be found in even the most extreme forms of renunciation.”—Entertainment Weekly “Ferocious.”—The New York Times Book Review (Ten Best Books of the Year) “Both terrifying and terrific.”—Lauren Groff “Provocative [and] shocking.”—The Washington Post Before the nightmares began, Yeong-hye and her husband lived an ordinary, controlled life. But the dreams—invasive images of blood and brutality—torture her, driving Yeong-hye to purge her mind and renounce eating meat altogether. It’s a small act of independence, but it interrupts her marriage and sets into motion an increasingly grotesque chain of events at home. As her husband, her brother-in-law and sister each fight to reassert their control, Yeong-hye obsessively defends the choice that’s become sacred to her. Soon their attempts turn desperate, subjecting first her mind, and then her body, to ever more intrusive and perverse violations, sending Yeong-hye spiraling into a dangerous, bizarre estrangement, not only from those closest to her, but also from herself.    Celebrated by critics around the world, The Vegetarian is a darkly allegorical, Kafka-esque tale of power, obsession, and one woman’s struggle to break free from the violence both without and within her. One of the Best Books of the Year—BuzzFeed, Entertainment Weekly, Wall Street Journal, Time, Elle, The Economist, HuffPost, Slate, Bustle, The St. Louis Dispatch, Electric Literature, Publishers Weekly

The Hurricane Wars: A Novel (The Hurricane Wars, ,, 2023)
The fates of two bitter enemies with opposing magical abilities are swept together in The Hurricane Wars, the spellbinding debut in a fantasy romance trilogy set in a Southeast Asia—inspired world ravaged by storms, perfect for fans of Sarah J. Maas and R. F. Kuang. The heart is a battlefield. All Talasyn has ever known is the Hurricane Wars. Growing up an orphan in a nation under siege by the ruthless Night Emperor, Talasyn has found her family among the soldiers who fight for freedom. But she is hiding a deadly secret: light magic courses through her veins, a blazing power believed to have been wiped out years ago that can cut through the Night Empire's shadows. Prince Alaric, the emperor's only son and heir, has been forged into a weapon by his father. Tasked with obliterating any threats to the Night Empire's rule with the strength of his armies and mighty Shadow magic, Alaric has never been bested. That is until he sees Talasyn burning brightly on the battlefield with the magic that killed his grandfather, turned his father into a monster, and ignited the Hurricane Wars. In a clash of light and dark, their powers merge and create a force the likes of which has never been seen. Talasyn and Alaric both know this war can only end with them. But a greater threat is coming, and the strange new magic they can create together could be the only way to overcome it. Thrust into an uneasily alliance, they will confront the secrets at the heart of the war and find, in each other, a searing passion—one that could save their world...or destroy it. An exquisite fantasy brimming with unforgettable characters, sizzling enemies-to-lovers romance, and richly drawn worlds, The Hurricane Wars marks the breathtaking debut of an extraordinary new writer.

The Takeover: A Novel (Open Road Media, 2012)
Heiress Maggie Radcliffe owns three glamorous villas overlooking Lake Nemi-and one houseguest will stop at nothing to take it all   When American heiress Maggie Radcliffe relocates to the enchanting Lake Nemi, just south of Rome, she does so wishing to live in tune with ancient pagan rhythms of art and nature. Constantly surrounded by a cast of quirky characters, Radcliffe finds her latest guest in the form of old friend-and unrepentant grafter-Hubert Mallindaine. Mallindaine claims to be a direct descendent of the goddess Diana, whose spirit is said to rest at Nemi. As soon as he arrives, Radcliffe's vast material wealth begins to slip quietly out the door. While Radcliffe attempts to evict Mallindaine from her house, a host of new problems arise, all threatening to destroy everything Radcliffe holds dear.   Bold and incisive, The Takeover is an acidic comedy about the clash between the conventions of old wealth and the inevitable tide of modernity.   This ebook features an illustrated biography of Muriel Spark including rare photos and never-before-seen documents from the author's archive at the National Library of Scotland.

Another Brooklyn: a novel (Amistad, an imprint of HarperCollinsPublishers, HarperCollins, HarperAudio, Harper Audio, 2016)
"For August, running into a long-ago friend sets in motion resonant memories and transports her to a time and a place she thought she had mislaid: 1970s Brooklyn, where friendship was everything. August, Sylvia, Angela, and Gigi shared confidences as they ambled their neighborhood streets, a place where the girls believed that they were amazingly beautiful, brilliantly talented, with a future that belonged to them. But beneath the hopeful promise there was another Brooklyn, a dangerous place where grown men reached for innocent girls in dark hallways, where mothers disappeared, where fathers found religion, and where madness was a mere sunset away."

Ride Around Shining: A Novel (HarperCollins, HarperCollins Publishers, 2014)
Longlisted for the PEN/Robert W. Bingham Prize for Debut Fiction. A provocative debut novel about a young white chauffeur and his wealthy black employer, an NBA player-a twenty-first century inversion of what we've come to expect stories of race and class to look like, and a discomfiting portrait of envy and obsession. Ride Around Shining concerns the idle preoccupations, and later machinations, of a transplanted Portlander named Jess-a nobody from nowhere with a Master's degree and a gig delivering takeout. He parlays the latter, along with a few lies, into a job as a chauffeur for an up-and-coming Trail Blazer named Calyph West and his young wife, Antonia. Calyph is black and Antonia is white and Jess becomes fascinated, innocuously at first, by all they are that he is not. In striving to make himself indispensable to them, he causes Calyph to have a season-ending knee injury, then brings about the couple's estrangement, before positioning himself at last as their perverse savior. In the tradition of The Talented Mr. Ripley, The Great Gatsby, and Harold Pinter's The Servant-not to mention a certain Shakespeare play about a creepy white dude obsessed with a black dude-Ride Around Shining tries to say the unsayable about white fixation on black culture, particularly black athletic culture, something so common in everyday life it has gone all but unaddressed.

The Color Purple Collection: The Color Purple, The Temple of My Familiar, and Possessing the Secret of Joy (The Color Purple Collection, ,, 2012)
Three powerful novels by Alice Walker, beginning with her masterpiece The Color Purple, and following characters as they are drawn into critical confrontations with history   The Color Purple is Walker's stunning, Pulitzer Prize–winning novel of courage in the face of oppression. Celie grows up in rural Georgia, navigating a childhood of ceaseless abuse. Not only is she poor and despised by the society around her, she's badly treated by her family. As a teenager she begins writing letters directly to God in an attempt to transcend a life that often seems too much to bear. Her letters span twenty years and record a journey of self-discovery and empowerment through the guiding light of a few strong women and her own implacable will to find harmony with herself and her home.    In The Temple of My Familiar, Celie and Shug from The Color Purple follow the lives of a brilliant cast of characters, all dealing in some way with the legacy of the African experience in America. From recent African immigrants, to a woman who grew up in the mixed-race rainforest communities of South America, to Celie's own granddaughter living in modern-day San Francisco, all must come to understand the brutal stories of their ancestors to come to terms with their own troubled lives.     Possessing the Secret of Joy portrays Tashi's tribe, the Olinka, where young girls undergo circumcision as an initiation into the community. Tashi manages to avoid this fate at first, but when pressed by tribal leaders, she submits. Years later, married and living in America as Evelyn Johnson, Tashi's inner pain emerges. As she questions why such a terrifying, disfiguring sacrifice was required, she sorts through the many levels of subjugation with which she's been burdened over the years.

A place for us: a novel (Penguin Random House, SJP for Hogarth, Random House Publishing Group, Books on Tape, 2018)
"The first novel from Sarah Jessica Parker's new imprint, SJP for Hogarth, A Place for Us is a deeply moving and resonant story of love, identity and belonging A Place for Us unfolds the lives of an Indian-American Muslim family, gathered together in their Californian hometown to celebrate the eldest daughter, Hadia's, wedding - a match of love rather than tradition. It is here, on this momentous day, that Amar, the youngest of the siblings, reunites with his family for the first time in three years. Rafiq and Layla must now contend with the choices and betrayals that lead to their son's estrangement - the reckoning of parents who strove to pass on their cultures and traditions to their children; and of children who in turn struggle to balance authenticity in themselves with loyalty to the home they came from. In a narrative that spans decades and sees family life through the eyes of each member, A Place For Us charts the crucial moments in the family's past, from the bonds that bring them together to the differences that pull them apart. And as siblings Hadia, Huda, and Amar attempt to carve out a life for themselves, they must reconcile their present culture with their parent's faith, to tread a path between the old world and the new, and learn how the smallest decisions can lead to the deepest of betrayals. A deeply affecting and resonant story, A Place for Us is truly a book for our times: a moving portrait of what it means to be an American family today, a novel of love, identity and belonging that eloquently examines what it means to be both American and Muslim -- and announces Fatima Farheen Mirza as a major new literary talent. "--

The Zigzag Way: A Novel (Houghton Mifflin Harcourt, 2014)
Eric is a newly minted historian just out of graduate school, plagued by self-doubt over both his past choices and his future options. With no clear direction, he follows his lover, Em, when she travels to the Yucatan for her scientific research, but ends up alone in this foreign place. And so he pursues his own private quest, tracing his family's history to a Mexican ghost town, where, a hundred years earlier, young Cornish miners-among them Eric's grandparents-toiled to the death. Now, in place of the Cornish workers, the native Huichol Indians suffer the cruelty of the mines. When he inquires into their lives, Eric provokes the ire of their self-appointed savior, Dona Vera. Known as the "Queen of the Sierra," Dona Vera is the widow of a mining baron who has dedicated her fortune to preserving the Huichol culture. But her formidable presence belies a dubious past.

In the Company of Men (Other Press, 2021)
-- In the Company of Men explores critical questions about how we cope with a global crisis and how we can combat fear and prejudice.

Convenience store woman (Grove Press, Blackstone Publishing, Grove Atlantic, 2018)
Keiko Furukura had always been considered a strange child, and her parents always worried how she would get on in the real world, so when she takes on a job in a convenience store while at university, they are delighted for her. For her part, in the convenience store she finds a predictable world mandated by the store manual, which dictates how the workers should act and what they should say, and she copies her coworkers' style of dress and speech patterns so that she can play the part of a normal person. However, eighteen years later, at age 36, she is still in the same job, has never had a boyfriend, and has only few friends. She feels comfortable in her life, but is aware that she is not living up to society's expectations and causing her family to worry about her. When a similarly alienated but cynical and bitter young man comes to work in the store, he will upset Keiko's contented stasis--but will it be for the better?

Yellowface: a novel (HarperCollins, HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, 2023)
"Authors June Hayward and Athena Liu were supposed to be twin rising stars. But Athena's a literary darling. June Hayward is literally nobody. Who wants stories about basic white girls, June thinks. So when June witnesses Athena's death in a freak accident, she acts on impulse: she steals Athena's just-finished masterpiece, an experimental novel about the unsung contributions of Chinese laborers during World War I. So what if June edits Athena's novel and sends it to her agent as her own work? So what if she lets her new publisher rebrand her as Juniper Song--complete with an ambiguously ethnic author photo? Doesn't this piece of history deserve to be told, whoever the teller? That's what June claims, and the New York Times bestseller list seems to agree. But June can't get away from Athena's shadow, and emerging evidence threatens to bring June's (stolen) success down around her. As June races to protect her secret, she discovers exactly how far she will go to keep what she thinks she deserves."--

The O'Briens: a novel (Recorded Books, Inc., Knopf Doubleday Publishing Group, Pantheon Books, 2012)
"A family saga spanning half a century in the lives of a restless and ambitious clan starts with the story of backwoods youth-turned-railroad magnate Joe O'Brien, who after leaving the Canadian wilds and sharing a passionate courtship with Iseult, becomes the patriarch of a family that sees the first airplanes, two world wars and the election of JFK. By the award-winning author of The Law of Dreams"--From publisher.

House of Broken Angels, The (Hachette Audio, 2018)
-- is Luis Alberto Urrea at his best, and cements his reputation as a storyteller of the first rank.

The Lowland: National Book Award Finalist; Man Booker Prize Finalist (Vintage Contemporaries, ,, 2013)
-- Shortlisted for the 2013 Man Booker Prize From the Pulitzer Prize-winning, best-selling author of -- The Lowland This ebook edition includes a Reading Group Guide.

Love, chai, and other four-letter words (Chai Masala Club romances, 1, 1, 2021)
"Kiran Mathur knows firsthand just how dangerous love can be. After all, her sister's marriage in India nearly destroyed Kiran's family. So she's decided to redeem romance herself-by not falling for anyone who might disappoint her parents. That is, until she meets her new neighbor Nash Hawthorne..."--
Anika Sharma

Breath, eyes, memory (Vintage contemporaries, ,, 1998)
At the age of twelve, Sophie Caco is sent from the impoverished village of Croix-des-Rosets to New York to be reunited with her mother, where she gains a legacy of shame that only be healed when she returns to Haiti, to the woman who first reared her.

The island of missing trees (Bloomsbury Publishing (US), Bloomsbury Publishing, 2021)
"Two teenagers, a Greek Cypriot and a Turkish Cypriot, meet at a taverna on the island they both call home. In the taverna, hidden beneath garlands of garlic, chili peppers and creeping honeysuckle, Kostas and Defne grow in their forbidden love for each other. A fig tree stretches through a cavity in the roof, and this tree bears witness to their hushed, happy meetings and eventually, to their silent, surreptitious departures. The tree is there when war breaks out, when the capital is reduced to ashes and rubble, and when the teenagers vanish. Decades later, Kostas returns. He is a botanist looking for native species, but really, he's searching for lost love. Years later a Ficus carica grows in the back garden of a house in London where Ada Kazantzakis lives. This tree is her only connection to an island she has never visited -- her only connection to her family's troubled history and her complex identity as she seeks to untangle years of secrets to find her place in the world. A moving, beautifully written, and delicately constructed story of love, division, transcendence, history, and eco-consciousness, The Island of Missing Trees is Elif Shafak's best work yet." -- A novel about belonging and identity, love and trauma, nature and renewal, from the Booker-shortlisted author of 10 Minutes 38 Seconds in This Strange World.

Behold the Dreamers (Random House, Random House Publishing Group, Penguin Random House LLC, 2016)
Jende Jonga, a Cameroonian immigrant living in Harlem has come to the United States to provide a better life for himself, and his family. In the fall of 2007, Jende can hardly believe his luck when he lands a job as a chauffeur for a senior executive at Lehman Brothers. When the financial world is rocked by the collapse of Lehman Brothers, Jende is desperate to keep his job and is soon forced to make an impossible choice.

Beyond the Horizon (Blackstone Publishing, 2021)
She points the lens of the camera. The artist turns his head slightly. The light catches his brow and his silver-white hair. She snaps. He is lit like a Vermeer. Ireland. County Wicklow, 1951. A father and son go swimming in the sea. The waves crash. The wind rises. Only one comes back-Colin, aged six. His mother, Eileen, runs to seek help, but this is a tragedy that will haunt them forever. Colin won't speak a word. He is mute and struggling to cope. But Eileen can see he has a talent for painting. She shows him his father's artwork and gives him a print of a Paul Henry landscape, and slowly, with her encouragement, he begins to follow his dream. Years later on Inishbofin island off the west coast of Ireland, out walking with his dog on the sand, Colin meets Laura, a young woman on holiday, and a tentative friendship starts to develop. Gradually his past comes to life in a story filled with love and frustration, loss and betrayal, but above all with the passion he has held through his life for the light in the sea and the sky and his search for that distant, elusive shore where the sky sweeps down to the water. One man. The sea. One painting.

The year of the runaways (Alfred A. Knopf, Knopf Doubleday Publishing Group, HighBridge, 2016)
The lives of three young men, and one unforgettable woman, intertwine over the course of one year after they immigrate from India to Sheffield, England.